O ensino dos modelos probabilísticos discretos no ensino médio - Santana, Jailson Santos (2016)
This work aims to support Basic Education teachers by providing a detailed materials for teaching Combinatorial Analysis, Probability and Probabilistic Models, taking into account aspects related to day-to- day using mathematical concepts in problem situations. We also propose a teaching sequence on the topics mentioned above for the Basic Education teachers to broaden and diversify their strategies education.